The Effect of Service Quality, Facilities, and Location on Guest Satisfaction at Truntum Hotel Padang - Al Hambra; Kahar, Azmen (Journal of Multidimensional Management, 2025)
This study examines the impact of service quality, facilities, and location on guest satisfaction at Truntum Padang Hotel, a four-star property in West Sumatra, Indonesia. Using a quantitative, causal-associative design, data were collected from 370 guests through a structured questionnaire employing validated SERVQUAL-based indicators and analyzed using multiple linear regression in SPSS 26.0. The results reveal that, collectively, the three independent variables significantly influence guest satisfaction (F = 94.530, p < 0.001). However, partial tests indicate that only facilities (β = 0.194, p < 0.001) and location (β = 0.233, p < 0.001) have significant positive effects, while service quality shows a positive but statistically insignificant relationship (β = 0.034, p = 0.223). These findings suggest that in this context, tangible attributes such as well-maintained amenities and strategic accessibility play a more decisive role in shaping guest perceptions than service interactions, particularly when baseline service standards are already met. The study offers practical implications for hotel managers to prioritize continuous facility upgrades and maximize location.